CEO Narcissism and Firm Performance: The Strategic Role of ESG Performance - Candy Candy; Elaine Wong; Robby Krisyadi (Annals of Management and Organization Research, 2026)
Purpose: This study investigates how CEO narcissism influences firm performance and examines whether Environmental, Social, and Governance (ESG) performance mediates this relationship. Research Methodology: A quantitative approach was used to analyze data from 75 purposively selected firms listed on the Indonesian Stock Exchange (IDX) for the period 2019-2023. Regression methods were applied to test direct and indirect relationships with financial performance indicators such as ROA and ROE. ESG performance is used as a mediating variable. Results: The study finds that CEO narcissism negatively affects ROA but positively influences ROE. ESG performance significantly impacts both ROA and ROE. The mediation analysis shows that ESG performance partially mediates the relationship between CEO narcissism and ROA but does not significantly mediate the relationship with ROE. Conclusions: CEO narcissism affects firm performance directly and indirectly through ESG performance, emphasizing ESG as a strategic pathway for executive characteristics to shape financial outcomes. Limitations: CEO narcissism was measured using photographs, which may introduce bias. This study is limited to Indonesian firms, which reduces generalizability. Contributions: This study contributes to corporate governance, leadership studies, and sustainability management by highlighting the influence of CEO traits on ESG-driven performance. This study extends the Upper Echelons Theory by incorporating ESG dimensions into the CEO-firm performance relationship.